STRATEGI KOMUNIKASI PENANAMAN NILAI-NILAI AGAMA ISLAM DI SD ISLAM MIFTAHUL FALAH - Sucilawati, (Jurnal Dakwah Tabligh, 2023)
Religious education is fundamental, particularly the moral part to be taught in the early process. Morality is the key to being smart intellectually, spiritually, and emotionally. It is the responsibility of parents, teachers, and the community to provide Islamic values for the students. For that, there must be a strategy for delivering these values. Some strategies that can be used to deliver religious values are (1) example or model, (2) habituation, (3) advice, and (4) punishment.